A general approach of unit conversion system in lattice Boltzmann method and applications for convective heat transfer in tube banks. (June 2019) - Huang, Ju'an; Bao, Cheng; Jiang, Zeyi; Zhang, Xinxin
Highlights: A general scaling system by analogy with Planck units for LBM simulations. A validated simulation for convective heat transfer in tube banks. A general boundary scheme for transport problems in LBM simulation. Abstract: A general unit conversion system based on the analogy with the Planck unit system is put forward in this article for most physical quantities in lattice Boltzmann simulations. Comparing with the traditional unit conversion methods, the approach has more systematic, programmatic and standardized operating process and can be applied in programming easily. In addition, a two-dimension exemplary simulation of convective heat transfer in tube banks is implemented to illustrate the feasibility and advantage of the approach, with verification of coupled flow and heat transfer by the empirical formula in literature. Furthermore, a uniform scheme for three kinds of boundary conditions for heat and mass transfer is developed and applied herein.